The Quality Management of Arabic Language Education Based on the Quality Management System (SMM) ISO 9001:2015 - Mochamad Iskarim (ALSINATUNA, 2018)
The study attempts at discussing the quality management with the Quality Management System (SMM) ISO 9001:2015 applied in the Arabic Language Education. The discussion focused on elaborating seven principles of SMM ISO 9001:2015, containing customer focus, leadership, engagement of people, process approach, continuous improvement, evidence-based decision making and management relationship. The quality management is expected to assist the Arabic language education to create quality, process and graduates who are well-prepared to compete both in the national and international levels. As a part of the process, the SMM ISO 9001:2015-based quality management elucidates a comprehensive guidance for the Arabic Language Education departments to continuously improve their system to fulfil the customer and the user satisfaction. Seen from the result, SMM ISO 9001:2015 can assist the educational institutions to produce graduates who are productive, capable and competitive in the national as well as global levels.